2021
DOI: 10.1039/d1na00211b
|View full text |Cite|
|
Sign up to set email alerts
|

Optimal centrifugal isolating of liposome–protein complexes from human plasma

Abstract: In the past few years, characterization of the protein corona (PC) that forms around liposomal systems has gained increasing interest for the development of novel therapeutic and diagnostic technologies. At...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…For SDS-PAGE and proteomics, lipoplexes-protein complexes were isolated by centrifugation for 15 min at 14 000 rpm. The pellets were washed three times with PBS to remove unbound proteins obtaining the “hard corona” (further details can be found in ref ( 55 )).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For SDS-PAGE and proteomics, lipoplexes-protein complexes were isolated by centrifugation for 15 min at 14 000 rpm. The pellets were washed three times with PBS to remove unbound proteins obtaining the “hard corona” (further details can be found in ref ( 55 )).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, gel images were acquired with a ChemiDoc gel imaging system (Bio-Rad, CA) and processed by means of custom MatLab scripts (MathWorks, Natick, MA), as previously reported. 55 …”
Section: Methodsmentioning
confidence: 99%
“…Each sample was loaded on a gradient polyacrylamide gel stain-free (4–20% TGX precast gels, Bio-Rad, Hercules, CA, USA) and run at 100 V for 150 min. Finally, gel images were acquired with a ChemiDoc™ gel imaging system (Bio-Rad, Hercules, CA, USA) and processed using custom MATLAB scripts (MathWorks, Natick, MA, USA), as previously reported [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…One-dimensional SDS-PAGE experiments were performed after protein corona isolation via centrifugation for 15 min at 4 • C, 21,400× g. Pellets were washed three times with PBS to remove unbound and loosely bound proteins and then resuspended in 20 mL of Laemmli Loading buffer 1× and boiled for 10 min at 100 • C. Each sample was loaded on a gradient polyacrylamide gel stain-free (4-20% TGX precast gels, Bio-Rad, Hercules, CA, USA) and run at 100 V for 150 min. Finally, gel images were acquired with a ChemiDoc™ gel imaging system (Bio-Rad, Hercules, CA, USA) and processed using custom MATLAB scripts (MathWorks, Natick, MA, USA), as previously reported [17].…”
Section: Sodium Dodecyl Sulphate-polyacrylamide Gel Electrophoresis (...mentioning
confidence: 99%
“…Consequently, contamination from biological nanoparticles was not examined and could not be excluded. However, previous studies indicated that it should produce minor, if any, effect on the size of liposome-protein complexes [16,17].…”
Section: Size and Zeta Potential Measurementsmentioning
confidence: 99%